Pascal and Theology - Miel, Jan (Johns Hopkins University Press, 2022)
The question of man's freedom to exercise his will—as active an issue among twentieth-century philosophers and theologians as it was in the Jesuit and Jansenist camps known to Pascal—is basic to this study. Pascal's theological thinking, which Professor Miel demonstrates to be the source of unity and coherence in virtually all phases of his thought, is preoccupied by a concern for man's limitations. In his analysis of Pascal's theology, Miel is concerned not only with characterizing Pascal's theological position but also with evaluating it in terms of the history of the church. In a concise and lucid review of the Christian doctrine of grace from the pre-Augustinians through the Renaissance, the author identifies the intellectual-theological atmosphere that created the need for Pascal's strong defense of Augustinian theology. Miel considers Pascal's Écrits sur la grâce, Lettres provincials, and Pensées as well as shorter compositions and correspondence. He establishes the content of Pascal's vision of grace and free will, noting both its originality and its sense of history. Most importantly, he asserts that Pascal's affirmation of Jansenism predated his association with Port Royal and, indeed, was basic to all his adult thought and work. The author finds in the writings of Pascal a style that anticipates twentieth-century theology, a sophistication that belies charges of Pascal's theological naïveté, and a concern to uphold rather than to undermine doctrinal traditions of the church.